Pengaruh Likuiditas, Profitabilitas, Struktur Modal, dan Harga Saham terhadap Kebijakan Dividen pada Perusahaan Consumer Goods - Purnasari, Nina; Sylvia, Sylvia; William, Vivian (E-Jurnal Akuntansi, 2020)
The purpose of the research is to know and analyze the influence of liquidity, profitability, capital structure and share price on dividend policy on Consumer Goods Companies listed on the Indonesia Stock Exchange period 2014-2018. This research uses quantitative research. Quantitative research approach. The nature of research is a causal relationship. The collection of this research data by means of documentation. The population of this study is 51 Consumer Goods Companies listed on the Indonesia Stock Exchange for the period 2014-2018. A research sample of 16 Consumer Goods Companies listed on the Indonesia Stock Exchange period 2014-2018. The research model is multiple linear regressions. The results of this study are Liquidity, profitability, capital structure and share price simultaneously and partially affect the dividend policy on Consumer Goods Companies.   Keywords: Liquidity, Profitability; Capital Structure; Share Price; Dividend Policy.